Analysis of Underwriting Activity and Its Impact on the Profitability Ratios of the Insurance Companies Listed in the Iraq Stock Exchange - Al-Zuhairi, Ahmed Khalaf Hussein (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
It is commonly accepted that the success and expansion of insurance companies' underwriting operations, which is indicated by the premiums received from insurance policies, is reflected in their profitability rates. During the period of 2010 to 2021, Iraqi insurance companies in the private sector that are listed on the Iraq Stock Exchange experienced a fluctuation in the increase and noticeable decrease of gross written premiums, which had a negative impact on their profitability ratios. The aim of this investigation is to analyze the underwriting activities carried out by all insurance companies that are publicly listed on the Iraq Stock Exchange spanning from 2010 to 2021, and assess the impact of these activities on the companies' profitability rates. To evaluate the profitability of these firms, three indicators are used, namely the rate of return on assets, return on equity, and profit margin ratio. The study employs Data Panel models using Eviews 12 to identify the research samples during the study period. Additionally, the pooled regression model is used to compare the findings and test the hypotheses of the study. In a structured manner, data is collected from the annual reports released by the Iraq Stock Exchange. The statistical examination of the findings reveals that the gross written premium has a significant and positive influence on all of the profitability ratios that were evaluated in this study, namely the rate of return on assets, return on equity, and profit margin ratio.